On a Method of Solving Non-Isothermal Two-Phase Filtration Problems - Gasimov, Sardar; Mammadov, Rashad (Proceedings of the Latvian Academy of Sciences. Section B, Natural Sciences, 2025)
A numerical method is considered based on the numerical modelling of the problem of a nonisothermal process of nonlinear filtration of two-phase fluid, taking into account relative phase permeabilities and capillary forces. Numerical implementation of the algorithm is carried out using the finite difference method on an adaptive grid. The proposed difference-iterative method in adaptive grids can be used to find a rational method for treating the oil layer. The following issues are studied by means of numerical calculations: assessment of the efficiency of hot water injection compared to cold water injection in the development of oilfields containing medium and high viscosity oils, impact of the periodicity of hot and cold water injection on the oil recovery, impact of preliminary water saturation on the ultimate oil recovery in case of hot water injection, and assessment of the impact of thermal effect on the oil recovery from the depletion layer.